CAN THE 14C PRODUCTION IN 1055 CE BE AFFECTED BY SN1054?. Issue 5 (18th October 2020) - Terrasi, F; Marzaioli, F; Buompane, R; Passariello, I; Porzio, G; Capano, M; Helama, S; Oinonen, M; Nöjd, P; Uusitalo, J; Jull, A J T; Panyushkina, I P; et al.
ABSTRACT: Annually resolved radiocarbon ( 14 C) measurements on tree rings led to the discovery of abrupt variations in 14 C production attributed to large solar flares. We present new results of annual and subannual 14 C fluctuations in tree rings from a middle-latitude sequoia (California) and a high-latitude pine (Finland), analyzed for the period 1030–1080 CE, to trace a possible impact of the Crab supernova explosion, occurring during the Oort minimum of solar activity. Our results indicate an increase of Δ 14 C around 1054/55 CE, which we estimate is higher in magnitude than the cyclic variability due to solar activity at a 2σ significance level. The net signal appears to be synchronized in the studied locations. Several sources of this event are possible including γ-rays from the Crab supernova, an unusually weak solar minimum or a solar energetic particle incident. More data are needed to provide more insight into the origin of this 14 C event.